Syndactyly in Pigs: A Review of Previous Research and the Presentation of Eight Archaeological Specimens. (2nd August 2011) - Madgwick, R.; Forest, V.; Beglane, F.
ABSTRACT: This paper reviews evidence for the rare condition of porcine syndactyly. It describes eight archaeological examples from Britain, Northern Ireland and France. Syndactyly refers to the partial or complete fusion of two or more adjacent phalanges on the medio‐lateral border. The degree and character of fusion are variable, but phalanges frequently unite to create a single skeletal element. This condition has been identified by veterinarians, zoologists and naturalists in individuals and populations in a range of species, but in spite of substantial research on the condition in humans and to a lesser extent cattle, it remains relatively poorly understood in other mammals. Syndactyly is generally agreed to be primarily congenital in origin, although factors affecting its incidence remain far from fully understood. In light of the general paucity of discussion of specific conditions of animal palaeopathology, this paper presents an analysis of these newly discovered syndactyle pig specimens, offers a review of research with particular reference to pigs and discusses the etiology of the condition. Copyright © 2011 John Wiley & Sons, Ltd.